Seed Quality Analysis Against Seed Repurchase Decisions Through Customer Satisfaction On CV. Rizky Nazwa Niezha - Sri Rindayani; Slamet Widodo; Nurafrina Siregar (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the effect of seed quality on seed repurchase decisions through customer satisfaction at CV. Rizky Nazwa Niezha. Seed quality is a key factor in determining customer satisfaction, which in turn can influence the decision to make a repeat purchase. The method used in this study is a survey with a quantitative approach, where data is collected through questionnaires distributed to customers of CV. Rizky Nazwa Niezha. The results of the analysis show that there is a significant positive relationship between seed quality and customer satisfaction. Customers who are satisfied with the quality of the seeds received tend to be more committed to making repeat purchases. In addition, customer satisfaction has been shown to act as a mediator between seed quality and repeat purchase decisions, indicating that improving seed quality can increase satisfaction and encourage repeat purchase decisions. This study provides recommendations for CV. Rizky Nazwa Niezha to continue to improve the quality of products and services in order to increase customer satisfaction and their loyalty. Thus, it is hoped that the company can maintain market share and increase business growth in the future.